Civil society and street politics: contesting state legitimacy through demonstrations in emerging democracies - Barlian, Jauchar; Mujiburrahman, Mujiburrahman; Budiman, Budiman; Syahid, Imam; Qolbi, Yahdi; Fichriyadi Hastira, Muh (Otoritas : Jurnal Ilmu Pemerintahan, 2026)
The wave of street demonstrations in Indonesia in recent years has highlighted tensions between the state and civil society, particularly when representative institutions are perceived as no longer capable of engaging in deliberative communication with citizens. This study aims to analyze street demonstrations as a political practice of civil society in response to the weakening of trust in formal democratic channels. This study focuses on a series of protests demanding the dissolution of the House of Representatives on August 25–31, 2025. This study used a phenomenological approach to analyze the symbolic and moral meanings emerging from the demonstrations. Data were collected through an analysis of media reports, civil society organization reports, official state documents, and social media content. The analytical process followed the Miles and Huberman model through data reduction, presentation, and conclusions. The findings indicate that when communication between the state and citizens is disrupted and public trust weakens, street politics emerges as a space to articulate criticism and ethical demands. The escalation of violence, differing narratives regarding the victims, and high public dissatisfaction with the handling of protests highlight the tension between electoral legitimacy and moral legitimacy. This study suggests that democratic legitimacy is dynamic and continuously negotiated through interactions between the state and civil society, as well as non-electoral participation in the public sphere.